2001
DOI: 10.1046/j.1360-0443.2001.961014559.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among problem drug users in Rome: an 18‐year follow‐up study, 1980–97

Abstract: AIDS mortality among drug addicts began to decrease earlier than expected; the decrease was particularly significant in the period 1993-94 for both sexes. Afterwards a continuous but slight decrease was observed among males only. Even though overdose mortality has also decreased slightly in recent years, we still observe high mortality levels for both overdose and all other causes. These findings suggest that interventions directed specifically towards the reduction of baseline mortality are still needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 28 publications
5
65
1
1
Order By: Relevance
“…A study involving drug users entering treatment in Rome, Italy, reported a similar SMR of 10.2 for respiratoryrelated death. 23 This is consistent with the observation that pneumonia is an important cause of morbidity and hospital admission among injection drug users. [24][25][26] The very high drug-related mortality and excess mortality in our study are consistent with prior findings among injection drug users in Vancouver 8 and elsewhere.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A study involving drug users entering treatment in Rome, Italy, reported a similar SMR of 10.2 for respiratoryrelated death. 23 This is consistent with the observation that pneumonia is an important cause of morbidity and hospital admission among injection drug users. [24][25][26] The very high drug-related mortality and excess mortality in our study are consistent with prior findings among injection drug users in Vancouver 8 and elsewhere.…”
Section: Discussionsupporting
confidence: 79%
“…[24][25][26] The very high drug-related mortality and excess mortality in our study are consistent with prior findings among injection drug users in Vancouver 8 and elsewhere. 13,15,23,27,28 Liverrelated mortality, which accounted for 6% of the deaths, was associated with an SMR of 5.9. Comparatively higher SMRs were reported in studies involving people taking opioid substitution therapy (SMR 17.0) 16 and among people infected with hepatitis B virus (SMR 10.0) and HCV (SMR 15.8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 1990s, several studies reported decreasing death rates due to HIV infection among drug users and attributed the downward trends to the new HIV medication regimens. 8,9 However, during the same period, other studies documented significant increases in drug overdose deaths in several countries. 10 -15 Notwithstanding these studies, the rates and causes of mortality of Hispanic drug users in the U.S. remain understudied.…”
Section: Introductionmentioning
confidence: 93%
“…Mortality studies in cohorts of problem drug users or injectors are arguably a better approach still (see Wahren et al, 1997;Versino et al, 2000;Langendam et al, 2001;Bargagli et al, 2001;Risser et al, 2001;Gossop et al, 2002;Hickman et al, 2003;Galai et al, 2003;Copeland et al, 2004;Bargagli et al, 2005;Bloor et al, 2008) because: a) they document not only drugsrelated but also HIV-related and other-cause mortality (see Ross, 2002 andBloor et al, 2008), b) the covariate influences of sex and current age on the risk of drugs-related death can be estimated for individuals whose drugs history, including treatment referral (Buster et al, 2002 andFugelstad et al, 2007), route of administration of primary drug and initiation age, was documented in a standardized manner at enrolment to the cohort (Hickman et al, 2003 andCopeland et al, 2004), and c) with shared protocol for enrolment, comparably-estimated risks can be compared across cohorts. , for example, applied evidence-synthesis techniques to published data from Scotland to deduce that the relative risk of drugs-related death per 100 injectors could be 1.8 times as high for males (95% CI: 1.3 to 2.3) and two to six times higher for older injectors.…”
Section: Introductionmentioning
confidence: 99%